Organisational Changes During Implementation Of An Information Systems Project - Sari, Cut Dhea Permata (Utami Publisher, 2024)
Changes in the organisation are inevitable when implementing an information system project. The information system implementation process involves the introduction of new technology, changes to business processes, and user adaptation to these changes. These changes can affect various aspects of the organisation, including structure, culture and employee behaviour. This abstract aims to analyse the changes in organisations that occur during the implementation of information systems projects. Firstly, structural changes can occur as a result of the introduction of a new information system. The organisation may need to update or change its hierarchical structure, division of tasks and communication channels to suit the needs of the new system. These changes can lead to organisational restructuring that is more efficient and responsive to technological demands. Secondly, cultural changes may occur as organisations adapt to changes in information systems. Organisational cultures accustomed to old ways of working may face resistance to change. However, through training and effective communication, organisations can build a culture that supports innovation, collaboration and adaptability. Positive cultural change is essential to ensure successful use of information systems. Thirdly, employee behaviour change is a critical component of information system implementation. Employees need to develop new skills, learn new workflows, and adapt to the changes brought about by information systems. Good training and strong management support can help reduce the uncertainty and anxiety that employees may experience during change. Employees who are able to adapt quickly and effectively will maximise the benefits of the implemented information system. In conclusion, the implementation of an information systems project brings about significant changes in the organisation. Structural, cultural and employee behavioural changes are important aspects that must be managed properly for a successful information system implementation. In the face of these changes, management must implement appropriate communication, training and support strategies to ensure good acceptance and adoption by all members of the organisation. Thus, organisational change can be an opportunity to create a more efficient, innovative and adaptive environment in the face of information technology development.